A review of current research progress on tensile behavior of expansion anchors in concrete. (December 2021) - Chen, Zhao
Abstract: Expansion anchors are one common type of post-installed concrete anchors. A review of the static tensile behavior of expansion anchors is conducted. Focuses of this study are on the working principle, failure modes, and prediction models of the ultimate tensile strength ( Nu ). Expansion anchors are divided into torque-controlled and displacement-controlled expansion anchors according to the installation method. Regardless of installation types, it is through the high expansion force and friction force to prevent the anchors from being pulled out. As effective embedment depth ( hef ) increases, dominant failure modes change from concrete breakout to pull-out/pull-through failure and finally reach steel failure. The main prediction models of ultimate tensile strength of expansion anchors in the concrete breakout mode include the Concrete Capacity Design (CCD), 45-degree, and variable angle cone method (VAC) methods. Among them, the CCD method shows good accuracy with test results and is adopted in many current standards. No prediction model on the pull-out/pull-through mode is included in the standards, while one recent individual study proposed a prediction model based on experimental and numerical results. This model shows a good agreement with test data and intersects with the CCD method at which hef failure modes change for different diameters. Further, the current research progress and limitations of the group effects, preset effects, numerical modeling, and abandoned hole effects on the tensile behavior of expansion anchors are discussed. More extensive and comprehensive research on these aspects is needed to guide the design and engineering practice.